Multiply the second equation by 2
2*(2x-4y)=2*(-13)
4x-8y= -26
Addition:
x+8y= -4
+
4x-8y= -26
5x+8y-8y= -4+(-26)
5x= -30 Divide wit 5
x= -6
x+8y= -4
-6+8y= -4
8y= -4+6
8y=2 Divide with 8
y=2/8 = 1/4
OR
2x-4y= -13
2*(-6)-4y= -13
-12+4y=-13
-4y= -13+12
-4y= -1 Divide with -4
y=(-1)/(-4)= 1/4
Select the best possible first step to solving the system by first eliminating the y variable.
x + 8y = –4
2x – 4y = –13
Multiply the first equation by 2.
Multiply the second equation by 2.
Multiply the first equation by –2.
Multiply the second equation by –2.
1 answer